Low Childhood Socioeconomic Status Promotes Eating in the Absence of Energy Need. (March 2016) - Hill, Sarah E.; Prokosch, Marjorie L.; DelPriore, Danielle J.; Griskevicius, Vladas; Kramer, Andrew
Life-history theory predicts that exposure to conditions typical of low socioeconomic status (SES) during childhood will calibrate development in ways that promote survival in harsh and unpredictable ecologies. Guided by this insight, the current research tested the hypothesis that low childhood SES will predict eating in the absence of energy need. Across three studies, we measured (Study 1) or manipulated (Studies 2 and 3) participants' energy need and gave them the opportunity to eat provided snacks. Participants also reported their SES during childhood and their current SES. Results revealed that people who grew up in high-SES environments regulated their food intake on the basis of their immediate energy need; they ate more when their need was high than when their need was low. This relationship was not observed among people who grew up in low-SES environments. These individuals consumed comparably high amounts of food when their current energy need was high and when it was low. Childhood SES may have a lasting impact on food regulation.